A comparative analysis of oral hygiene practices and daily dietary habits between dental and Allied health sciences students: An observational study - Farah Qaisar; Aneela Qaiser; Ayesha Irfan; Sanam Ayesha; Mahnoor Asif; Afshan Kamran Hussain (Journal of University Medical & Dental College, 2025)
BACKGROUND AND OBJECTIVE: Oral hygiene and dietary habits play important roles in maintaining a healthy lifestyle. Undergraduate students of allied health sciences and dentistry need to have adequate knowledge of diet and nutrition. This study aims to find out the Oral hygiene practices and daily dietary habits of dental and Allied health sciences students in order to assess their knowledge and health priorities. METHODOLOGY: Dietary and oral hygiene practices of 224 (n=112) undergraduate dental and Allied Health Sciences students from two local dental colleges were surveyed for this cross-sectional study using a convenience sampling technique. A semi-structured close-ended questionnaire was employed to collect data after taking informed consent. Data was analyzed using SPSS version 23. The results are presented as percentages and p < 0.05 was considered significant. RESULTS: The comparison of oral hygiene practices among undergraduate BDS and AHS students using a semi-structured closed-ended questionnaire showed statistical significance in different variables, including routine brushing (p<0.05), dental flossing (p=0.004), and dental consultation (p=0.048), indicating that dental students were more conscious about oral hygiene than the AHS group. In contrast, the comparison of dietary habits of both undergraduate groups did not show any significant difference, except for fruit and vegetable intake. Allied Health students showed better intake of fruits and vegetables (p < 0.05). CONCLUSION: Dental students demonstrated better oral hygiene practices compared to Allied Health Sciences students, reflecting greater awareness and adherence to the recommended oral care routines. However, Allied Health students exhibited better dietary habits, particularly with a higher intake of fruits and vegetables. These findings suggest the need for targeted educational interventions to address gaps in oral hygiene and dietary habits among undergraduate students in both fields.